High speed manufacturing of aluminum alloy 7075 tubing by Shear Assisted Processing and Extrusion (ShAPE). (November 2021) - Whalen, Scott; Olszta, Matthew; Reza-E-Rabby, Md.; Roosendaal, Timothy; Wang, Tianhao; Herling, Darrell; Taysom, Brandon Scott; Suffield, Sarah; Overman, Nicole
Abstract: Shear assisted processing and extrusion (ShAPE) was used to extrude aluminum alloy 7075 tubing at speeds up to 12.2 m/min without surface tearing. This work presents the first experimental evidence for high-speed extrusion of 7075, which improves upon conventional extrusion where 2.0 m/min is the limit. The increased speed is primarily attributed to more extensive shear deformation, compared to conventional extrusion, which results in a high density of low angle grain boundaries that facilitate continued deformation and delay the onset of surface tearing. Mechanical testing after heat treating to the T6 condition provided an ultimate tensile strength of 565.3 ± 4.6 MPa, yield strength of 495.7 ± 8.7 MPa, and elongation of 16.4 ± 1.0%. Strength values exceed the ASTM International minimum standard and are on par with American Society for Metals (ASM) typical values, while elongation was substantially improved compared to 7 and 11% for the ASTM and ASM values respectively. It was observed that low temperature extrusion at 341 °C and 40 rpm gave superior material properties in the T6 condition compared to high temperature extrusion at 441 °C and 120 rpm because of variances in nanoscale second phase size and distribution. Graphical abstract: Unlabelled Image Highlights: ShAPE extrusion of 7075 tubing performed at 12.2 m/min without tearing Tensile properties exceed the ASTM minimum standard and are on par with ASM typical values. Low temperature (341 °C) gave superior tensile properties compared to high temperature (441 °C). Process parameters were correlated with extent of nanoscale strengthening precipitates.